Zmiany w strukturze geograficznej handlu zagranicznego Indonezji wskutek kryzysu roku 1997 w regionie i poza regionem ASEAN - Prokurat, Sergiusz (Changes in Indonesian international trade’s geographical structure in and beyond ASEAN as a result of the 1997s crisis, 2009)
This paper proves that when comparing the factual situation before and after 1997s crisis the major difference in Indonesia’s manner of dealing with the task of international trade has appeared. The economic recession was not only “the Asian banking system’s crisis”, as it is being often called, but also, in case of Indonesia, the depression of international trade - in ASEAN itself and beyond the structure too. The monetary and banking system’s problems had an impact on the country’s currency exchange rate as well. Distrust of Indonesia had appeared causing the change in the country’s international trade’s geographical structure. The occurrence was particularly visible in Indonesian trade rates concerning countries beyond ASEAN region
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 262-272